Construção exata de sólitons de Hopf - Bonfim, A. C. R. do [UNESP] (2007)
ur object of study are classical field theories which possesses topological solitons and have a infnite number of conserved quantities .In particular our models have what is know as Hopf charge. This charge appears because, for finite energy solutions, our theories define mappings of a compactified space time in a 'S POT. 2' target space. We show that ours models's set of conserved quantities are related to the invariance of the Lagrangean under area preserving diffeomorphisms of the target space. Our models are closely related to the Skyrme-Faddeev model and so we give a brief introduction to it. Using Lie's method we find the symmetries of the Euler-Lagrange equations of such models, for an arbitrary curved space time. The symmetry condition turns out to be related with the solution of the Killing equations in a given space time. We then solve the corresponding equations for some specific examples, like the Euclidean, Minkowski and the 'S POT. 3' X R space times. Then, for the'S POT. 3' X R models, using the symmetries already found, we are able to find systems of coordinates for which then exists ansätze leading to separations of variables and to the reduction of the Euler-Lagrange equations (initially PDEs) to ODEs. These ODEs are linear and so we are able to integrate then and also to calculate all of the physically meaningful conserved quantities, as the energy, Hopf charge, angular momentum. We also explain why such ansatz leads to a linear ODE in this particular case and why the Lie integration algorithm works